Characteristics Of Kombucha From Various Herbal Tea Leaves - Nur Agustin Mardiana; Domas Galih Patria; Dwi Retnaningtyas Utami; Rinda Kusumawati; Sutrisno AdiPrayitno; Chusnul Chotimah (Food Science and Technology Journal (Foodscitech), 2022)
Kombucha has been well-known as functional food in Asia. Regular kombucha is produced using Camellia sinensis tea leaves. However, kombucha can also be produced from other substrates. This study aim to investigated characteristic of kombucha from various herbal tea by determine flavonoid content, phenolic content, antioxidant content and sensory. This study was conducted using Randomized Block Design with one factor and two duplicates of each treatment. Based on 8 day fermentation, bebuas (Premna pubescens Blume) has the highest phenolic content (926,19 µg/ml GAE), flavonoid content (391,81 µg/ml), and antioxidant activity IC50 values were 18,16 µg/ml. On the other hand, based on the sensory evaluation of kombucha (aroma and taste) panelists prefer indian jujube, while panelists prefer regular tea for color parameters